FORMATION OF METHODICAL BASE OF MANAGEMENT OF BUSINESS VALUE - K. Bykovskaya (Publishing House of the State University of Management, 2018)
The methodical basics of management of business value are covered, the conceptual framework on sources of special literature is specified. As definitions of the term «business value» strongly differ owing to its complexity and discrepancy, authors have tried to give own definition of a concept. Besides, authors allocate estimated indicators between which the narrowness of interrelation and their influence on business value have been defined. Results of a research of traditional tools of estimation of cost of business are also presented, the possibility of his use in management of business value by selection of necessary elements for the effective organization of this process is considered.